The HUPO Human Proteome Project (HPP), a Global Health Research Collaboration - Omenn, Gilbert S. (Cent Asian J Glob Health, 2012)
The global Human Proteome Project (HPP) was announced by the Human Proteome Organization (HUPO) at the 2010 World Congress of Proteomics in Sydney, Australia, and launched at the 2011 World Congress of Proteomics in Geneva, Switzerland, with analogies to the highly successful Human Genome Project. Extensive progress was reported at the September 2012 World Congress in Boston, USA. The HPP is designed to map the entire human proteome using available and emerging technologies. The HPP aims to create a molecular and biological foundation for improving health globally through better understanding of disease processes, more accurate diagnoses, and targets for more effective therapies and preventive interventions against many diseases. There are opportunities for individual investigators everywhere to access advanced datasets and to join HPP research teams.